Analisis Semiotika pada Poster Serial Netflix The Influencer Berdasarkan Teori Roland Barthes - Hendi Thamrin (Lembaga Pengembangan Kinerja Dosen, 2024)
Film and television series posters play a crucial role as both promotional media and symbolic representations of a work’s narrative and themes. This study analyzes the semiotics of the Netflix series The Influencer (2024) poster, which highlights issues of social media manipulation, identity crisis, and digital power. Its success in reaching Netflix’s Top 10 in Indonesia indicates strong cultural resonance. Using a qualitative approach with Barthes’ semiotic method, this research examines visual elements such as color, typography, and composition to reveal the poster’s denotative, connotative, and mythological meanings. The poster functions not only as a promotional tool but also as a medium conveying complex social messages.This study contributes to the field of Visual Communication Design by providing insights into how visual elements shape meaning and audience perception. The findings are expected to serve as a reference for academics and practitioners in understanding and creating posters that are both aesthetically appealing and meaningful.